A Modified Technique for Filter Paper Disc Chromatrography - Rizk, M.S. (Asian Journal of Chemistry, 2010)
A modified disc desiccator technique is described, which proved to be simpler, more accurate and gave better results than any other paper disc technique. All conditions concerning the modified technique are discussed.